2004
DOI: 10.1111/j.1440-1827.2004.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor‐like follicular dendritic cell tumor of the spleen

Abstract: A case of so-called inflammatory pseudotumor (IPT), occurring in the spleen of a 77-year-old woman, is reported. The spleen contained a well-circumscribed mass with central hemorrhage and necrosis. Histologically, spindle cells were dispersed in a background of abundant inflammatory cells, predominantly lymphocytes and plasma cells. The cells possessed enlarged, sometimes twisted or irregularly folded, nuclei that contained vesicular chromatin, and small but distinct, centrally located nucleoli. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…First, as outlined in this review study, five of six hepatic FDCs exhibited positive EBER by in situ hybridization, whereas none of the 24 extrahepatic cases tested was positive for the virus. EBV has also been demonstrated in some but not all splenic and nodal FDC sarcomas [6,26]. In the hepatic cases, Southern blotting analysis showed that the EBV infection occurred before the clonal proliferation of neoplastic FDCs, suggesting its causative role in the development of FDC sarcoma [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…First, as outlined in this review study, five of six hepatic FDCs exhibited positive EBER by in situ hybridization, whereas none of the 24 extrahepatic cases tested was positive for the virus. EBV has also been demonstrated in some but not all splenic and nodal FDC sarcomas [6,26]. In the hepatic cases, Southern blotting analysis showed that the EBV infection occurred before the clonal proliferation of neoplastic FDCs, suggesting its causative role in the development of FDC sarcoma [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…4 with EBV positivity have been reported. 2,4,[6][7][8][9][10][11][12] Ten of 19 cases have been described their imaging findings (Table 2). [6][7][8][9][10][11][12] Of them, CT findings were described in 8 cases, all of which showed a well circumscribed margin.…”
Section: Discussionmentioning
confidence: 99%
“…From 1996 to date we retrieved 22 publications reporting IPT-like FDC tumors [11,15,35,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. There were 46 patients described: 24 female, 22 male (ratio 1.1:1), median age 57y (range 29-79y).…”
Section: Follicular Dendritic Cell Tumors Of the Spleenmentioning
confidence: 99%